The Indonesian EFL Learners’ Motivation and Autonomy - Melvina (JURNAL PENDIDIKAN DAN PENGEMBANGAN MANUSIA, 2023)
A successful autonomous learner is usually influenced by numerous factors. Motivation is one of the main factors that have a connection and the greatest influence associated with it. The research focuses to scrutinize the link between motivation in learning and learner autonomy of Indonesian learners in learning English. It also aims to identify the significant difference between gender and degree level of study in motivation and autonomy. The investigation was conducted using a sample of forty university students from some provinces in Indonesia. The participants were given a questionnaire to assess their motivation in and autonomy in learning English. Pearson’s Product-Moment Correlation and independent-samples T-test were operated in analyzing the data gotten. The statistical analysis results revealed a positive correlation between learning motivation and learner autonomy. It also found that insignificant difference between male and female and between undergraduate and postgraduate learners in motivation and autonomy. The result of the research recommends the vigorous role of motivation and autonomy in teaching English, especially in the EFL context. They should have plenty of attention, as they may direct to more efficacious pedagogy.